Neuropathic Pain: Mechanism, Representation, Management and Treatment - Seddighi, Amir Saied; Seddighi, Afsoun; Ghadirian, Mahsa; Zali, Alireza; Tabatabaei Far, Seyed Mahmoud (International Clinical Neuroscience Journal, 2022)
Despite the development of screening tests and diagnostic tools, neuropathic pain is still identified as an underdiagnosed condition lacking proper epidemiological studies. It is difficult to estimate its incidence and prevalence the population. The objective of this narrative review is to summarize current knowledge concerning complications. The underlying mechanisms have also been reviewed in the development of diagnostic or treatment strategies in patients with neuropathic pain to investigate its unique symptoms. The main focus is concentrated on expansion of possible therapeutic options for neuropathic pain treatment. Many therapies are not effective and this often leads to a significant deterioration in the patients’ quality of life. So, the crucial and strategic role of therapeutics in guiding patients in the right direction should not be overlooked. The existing knowledge is so limited and has safety risks. It is truly important to provide alternative treatment strategies in selected patients with refractory neuropathic pain. Interventional therapies include different types of effective treatments for reducing neuropathic pain. Giving insight into recent findings on mechanisms of neuropathic pain may help understand and further develop strategies for correct diagnosis and successful treatment.